2022
DOI: 10.35516/jjps.v15i1.291
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and in vitro antioxidant activity analysis of leaf and callus extracts of Allophylus serratus (ROXB) KURZ.

Abstract: Allophylus serratus is an important medicinal plant whose leaves, fruits, roots and stem have been in use in traditional medicines. The present study is aimed to carry out preliminary phytochemical analysis and to determine antioxidant activity of leaf and callus water, methanol, ethyl acetate, chloroform and petroleum ether extracts of A. serratus. The extracts were subject to various qualitative and quantitative tests for phytochemical analysis. An in vitro antioxidant activity of the extracts was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Phytochemical screening is essential for the identification of lead components that possess pharmacological activities (24). These include primary (proteins, carbohydrates, and lipids) and secondary metabolites (Polyphenols, tannins, flavonoids, alkaloids and saponins) (25). Our present study reported the presence of phytochemical constituents in Melia azedarach.…”
Section: Aggregation Assaymentioning
confidence: 54%
“…Phytochemical screening is essential for the identification of lead components that possess pharmacological activities (24). These include primary (proteins, carbohydrates, and lipids) and secondary metabolites (Polyphenols, tannins, flavonoids, alkaloids and saponins) (25). Our present study reported the presence of phytochemical constituents in Melia azedarach.…”
Section: Aggregation Assaymentioning
confidence: 54%
“…Although many species and types of raspberries exist, red and black berries are the most common [9]. Recent research indicates that raspberry leaves and fruits are a rich source of flavonoid derivatives, represented by quercetin derivatives as well as phenolic acids, organic acids, and vitamin C [10]. Durgo et al [11] have declared that ellagic acid is the main component among phenolic compounds.…”
Section: Evaluation Of Anti-inflammatory…mentioning
confidence: 99%
“…Regarding the background and disadvantage of chemotherapy, essential oils (EOs) as anticancer therapeutic agents are being widely explored in recent years. EOs are natural oils secreted as secondary metabolites in aromatic plants 13,14 .…”
Section: In-vitro Assessment…mentioning
confidence: 99%